Jacob Faithful - Marryat, Frederick, 1792-1848 (Salt Lake City, UT : Project Gutenberg, 2007)
"Jacob Faithful" by Captain Frederick Marryat is a novel written in the early 19th century. The story chronicles the unique life and adventures of Jacob Faithful, a boy raised on a small river-barge called a lighter navigating the River Thames in London. The book promises an engaging exploration of Jacob's upbringing, as well as a vivid portrayal of life along the Thames during this period. At the start of the narrative, Jacob introduces himself, recounting the peculiarities of his parents and the unfortunate sequence of events that lead to him becoming an orphan at a young age. His mother, plagued by a drinking problem, meets a tragic end, while his father$1 (Bs drinking habits result in his demise in the river. Left alone at just eleven years old, Jacob takes charge of the lighter but is soon drawn into a new life on land as he navigates the challenges of growing up as a charity schoolboy. The opening chapters set the stage for Jacob's journey from a carefree boy of the river to a more complex character as he adapts to the realities of his circumstances and future prospects. (This is an automatically generated summary.)s
Release date is 2007-05-21
Produced by Nick Hodson of London, England
Keywords: Orphans -- Fiction; Sea stories; Thames River (England) -- Fiction; Picaresque literature; Seafaring life -- Fiction; Great Britain -- History, Naval -- 19th century -- Fiction; Great Britain. Royal Navy -- Officers -- Fiction; Barges -- Fiction